THU0157 REASONS FOR NON-PARTICIPATION IN A RANDOMIZED CONTROLLED TRIAL COMPARING TWO SEASONAL INFLUENZA VACCINES IN RHEUMATOID ARTHRITISPATIENTS. (June 2019) - Useche, Mariana; Starr, Jonathan; Rodriguez, Katherine; Ramanakumar, Agnihotram; Hudson, Marie; Ward, Brian; Colmegna, Ines
Abstract : Background: Low recruitment rates (12%) into influenza vaccine studies are reported among healthy older adults. Fear of side effects, lack of insight into personal risk status, and doubts about vaccine efficacy are the most commonly reported reasons for non-participation 1 . Rheumatoid arthritis (RA) patients are also at high risk for influenza and benefit from yearly immunization 2 . A number of influenza vaccines are currently available; however, it is unknown which vaccine(s) provides optimal protection to RA patients. Estimating participation rates is key for designing studies to address that issue. Objectives: To define the rate of non-participation and reported reasons for refusing entry into a randomized clinical trial (RCT) comparing two influenza vaccine formulations (NCT02936180 - ClinicalTrials.gov). Methods: Seropositive RA patients from McGill University Health Centre, on stable treatment prior to recruitment (≥3 months), were invited by their treating rheumatologists to participate in the study. A vaccine nurse contacted participants from Year 1 (Y1) and those from Year 2 (Y2) encountered a recruiter immediately after their rheumatologist's appointment. Patients who agreed to participate signed the consent form and were later contacted by a vaccine nurse to schedule their appointment. Reasons for non-participation were documented. Results: Over two influenza seasons, 692 RA patients were invited to participate in the study. The non-participation rate was 59.5% (Y1=64.6%, Y2= 53.1%, p=0.1). Non-participants and participants did not differ in age or sex (age mean±SD: 61.7±14.7 vs 60.9 ±12.9, p=0.5; female sex%: 76.8 vs 79.9, p=0.33). Inclusion and exclusion criteria resulted in the loss of 17 (4.1%) and 19 (4.6%) subjects, respectively. The three most commonly reported reasons for non-participation were vaccine misconceptions (n=49, 20.4%), reluctance to participate in a clinical trial (n=35, 14.6%), and lack of available time (n=29, 12.1%). Thirty-one patients reported more than one reason for non-participation. Reasons for non-participation were similar according to sex and patient age (> or < 65 years). Conclusion: Only half of eligible RA patients accepted to be enrolled in this influenza vaccine study. Enhancing patient literacy on vaccines and the relevance of conducting clinical trials is essential to optimize both recruitment to such trials and immunization rates. References: [1] Allsup SJ, Gosney MA. Difficulties of recruitment for a randomized controlled trial involving influenza vaccination in healthy older people. Gerontology. 2002; 48:170–173. [2] Blumentals WA, Arreglado A, Napalkov P, Toovey S. Rheumatoid arthritis and the incidence of influenza and influenza-related complications: a retrospective cohort study. BMC Musculoskelet Disord. (2012) 13:158. Acknowledgement: The Arthritis Society - Canada Disclosure of Interests: Mariana Useche: None declared, Jonathan Starr: None declared, Katherine Rodriguez: None declared, Agnihotram Ramanakumar: None declared, Marie Hudson Grant/research support from: Unrestricted research funds from Bristol-Myers Squibb, Brian Ward: None declared, Ines Colmegna: None declared